MOLECULAR DOCKING STUDIES OF SIDDHA HERBAL FORMULATION KUPPAIMENI CHOORNAM ON HUMAN HISTAMINE RECEPTOR (3RZE) - Gayatri, R.; Vinayak, S; Elansekaran, S (International Journal of Ayurveda and Pharma Research, 2019)
Background: Molecular docking has tremendous applications in the field of Siddha medicine especially herbal formulations were the interactions of the lead molecules of the formulation with that of receptors can be elucidated at the molecular level and furthermore to reach an assumption of its fundamental biochemical processes to which the formulation is targeting. Kuppaimeni Choornam (KC) is a simple herbal formulation used in Siddha medicine for urticaria and other skin allergies. As far as skin allergy is concerned Amino acids such as Asparagine (ASN), Tryptophan (Trp), Aspartate (Asp), Tyrosine (Tyr), Serine (Ser), Isoleucine (Ile), Lysine (Lys), Threonine (Thr), Phenylalanine (Phe) are the main core residues involved in mediating Human histamine receptor (3RZE). Binding of lead compounds with this core residue may inhibit the enzyme activity. Aim & Objectives: Molecular docking studies of Siddha herbal formulation KC and to screen the lead component interaction on the Human Histamine Receptor (3RZE). Methodology: Docking calculations were carried out using Auto Dock 4. Gasteiger partial charges were added to the ligand atoms. Docking simulations were performed using the Lamarckian genetic algorithm (LGA) and the Solis & Wets local search method. Initial position, orientation, and torsions of the ligand molecules were set randomly. All rotatable torsions were released during docking. Results and Conclusion: The compounds present in KC like beta-sitosterol, apigenin, luteolin, cuminaldehyde, kaempferol, and triacetonamine showed maximum interactions with 3RZE when compared to that of the standard cetirizine. Hence, these compounds of test drug possess promising Human histamine 1 receptor (3RZE) inhibition activity. For prospective pharmacological validation of Kuppaimeni Choornam, the docking studies were an important step for its scientific justification.